2019
DOI: 10.3389/fonc.2019.00501
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic Acid Reverses the Chemoresistance of Breast Cancer Cells to Paclitaxel by Targeting MiRNA-149-5p/MyD88

Abstract: Paclitaxel (PTX) is widely used as a front-line chemotherapy for breast cancer treatment. However, its clinical applications are limited by the development of chemoresistance. The objective of this study was to investigate the reversal effects of ursolic acid (UA) on PTX resistance and the possible mechanisms in breast cancer. The role of miRNA-149-5p/MyD88 in the regulation of PTX resistance was investigated by the transfection of breast cancer cells with MDA-MB-231 (231) and MDA-MB-231/PTX-resistance (231/PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 41 publications
0
39
0
1
Order By: Relevance
“…The miRNA-149 plays a significant role in suppressing different oncogenes and is frequently downregulated in BC. Overexpression studies with miRNA-149 demonstrated an inhibition of PI3K/AKT signaling pathway and MyD88 and a reverse of resistant to sensitive phenotype [ 168 ]. Additionally, an alkylating agent temozolomide exerted its anticancer effect by downregulating glucose metabolism.…”
Section: Modulating Glucose Metabolism To Increase the Anticancer mentioning
confidence: 99%
“…The miRNA-149 plays a significant role in suppressing different oncogenes and is frequently downregulated in BC. Overexpression studies with miRNA-149 demonstrated an inhibition of PI3K/AKT signaling pathway and MyD88 and a reverse of resistant to sensitive phenotype [ 168 ]. Additionally, an alkylating agent temozolomide exerted its anticancer effect by downregulating glucose metabolism.…”
Section: Modulating Glucose Metabolism To Increase the Anticancer mentioning
confidence: 99%
“…Although miRNAs only account for 1% of human genes, they can modulate up to 30% of human genes, making them the critical epigenetic regulators. Previous studies have identified the miR‐149/MyD88 axis in macrophages and breast cancer cells; however, it is still unclear whether this axis exists in NSCLC cells and regulates the stemness of NSCLC cells.…”
Section: Introductionmentioning
confidence: 99%
“…Here, this study found that UA, at a concentration of 10–20 μM, strongly inhibits cell viability in SK-HEP-1 (Figure 4A), Huh7 (Figure 4B), and Hep3B (Figure 4C) cells. Although the regulatory mechanism by which UA exerts anti-proliferative effects is not clear, large numbers of previous evidences have also shown that UA attenuates cell growth in multiple types of cancer cells, such as colorectal [11], breast [55], gastric [56], and melanoma [57]. Consistently, our results also show that UA was sufficient to decrease cell viability in lung (A549 and H1666), breast (MCF7 and MDA-MB-231), melanoma (A375 and A2058) and cervical (HeLa) cancer cells (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%